Profil Nutrisi dan Kualitas Sensori Produk Sereal Jewawut dengan Subsitusi Teh Hijau - Indrastuti; Syahmidarni Al Islamiyah; Vania Canisa Basma (Universitas Sulawesi Barat, 2023)
The millet that is processed into cereals are polished barley. The cultivation of barley causes a reduction in phenolic levels which correlates with antioxidant activity. Substitute green tea to increase levels of phenolic compounds in millet cereals. The purpose of this research was to make millet cereal products with the substitution of green tea as functional food and to determine the phenol content, nutritional content, and consumer acceptance. This research was conducted in two stages. The first stage was making millet cereal and the hedonic test on 15 panelists. The second stage was testing the phenol content and nutritional content of the best-formulated millet cereal based on the hedonic test. The results showed that the best millet cereal formulation based on the hedonic test for taste was the addition of 5% green tea (P1), with an increase in phenol levels from 546.54 ppm (P0) to 593.79 ppm. The nutritional content of millet cereal, namely water content of 5.43%; crude protein content 12%; crude fiber content 2,34%; BETN levels 75.10. From this research, it was found that green tea substitution increased the phenol content of millet cereal, nutritional content and for taste was acceptable to consumers with the addition of 5% green tea.